The Ahmadiyya Movement: Transforming from a Theological to a Social Movement - Trikarno Wulandari; Indo Santalia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This article examines the transformation of the Ahmadiyya Movement from a theological movement into a global social movement. Founded by Mirza Ghulam Ahmad in Qadian, India, in 1889, the Ahmadiyya emerged as a response to the spiritual decline of Muslims and the dominance of British colonial power. Initially focused on theological reform emphasizing non-legislative prophethood and continuing revelation, the movement gradually evolved into a transnational social organization promoting peace, tolerance, and humanitarian values. This study employs a qualitative approach using a literature review method by analyzing academic sources and official Ahmadiyya publications. The findings indicate that through its global Caliphate system and humanitarian network such as Humanity First, the Ahmadiyya has successfully transformed its identity from a controversial religious sect into a global social movement that promotes the message of peaceful Islam under the motto “Love for All, Hatred for None.